Judicial cooperation and sub-national integration Chile-Argentina: main achievements and developments - Sfeir Tonsic, Alejandro (Revista Tribuna Internacional, 2014)
The judicial cooperation developed between several organs of the Argentine provinces and regions of Chile, under the Treaty of Maipú on Integration and Cooperation (2009) and the Committees of bi-national integration, has experienced substantial progress in recent years, which are reflected in different activities described in this article, which have been coordinated and led by the Foreign Ministries of the two countries. Meanwhile, the bilateral judicial cooperation is intertwined with the concept of sub-national integration by allowing both a broad meeting of senior officials and professionals interested in advancing in these areas, as to make possible the narrowing of the existing links on both sides of the Andes. As a result of discussions in Mendoza in the “Cristo Redentor” Committee on 1 and 2 September 2011, and the organization of the First International Seminar on Judicial Cooperation Chile-Argentina on 29 and 30 March 2012 were able to implement new Commissions on Judicial cooperation in other Integration Committees and organize new seminars on such issue, in order to advance the field of judicial cooperation and integration. This article aims to report on the main achievements and developments in this area.